The Pattern of Anosmia in Non-hospitalized Patients in the COVID-19 Pandemic: A Cross-sectional Study - Elsherief,Hossam (2021)
Abstract Introduction It is now evident that the loss of smell and/or taste may be consistent accompanying symptoms of the SARS-CoV-2 infection. Objective To estimate the social behavior of recent anosmic non-hospitalized patients in the COVID-19 pandemic and to try to obtain the natural pattern in society in a cross-sectional study. Methods A cross-sectional study conducted on 4,860 patients with anosmia complaints during the COVID-19 pandemic. Patients who needed a consultation for an anosmia complaint confirmed that they had completed the survey regarding age, gender, history of general diseases, history of nasal disease, associated COVID-19 symptoms, smoking, blood group, and risk factors. Results A total of 4,860 patients with a mean age of 34.26 ± 11.91 years completed the study. There was a predominance of female patients: 3,150 (58.9%). Most patients (4,083 patients; 83%) developed sudden anosmia. In 85% (4131 patients) of the patients, a previous history of contact with anosmic patients was present. The most prevalent blood group was O (39%). In total, 67.4% of the patients underwent medical treatment. A history of unusual influenza attacks in December 2020 was reported by by 27% (1312 patients) of the patients. Conclusion Despite large diversity of behaviors among anosmic patients in the COVID-19 pandemic, we can observe a great similarity in the pattern of anosmia in non-hospitalized patients, especially in the way it spreads, the predisposing factors, and the individual recovery.